Improvement of the instrumental and technological design process of granule formation in the production of fertilizer grade «Superagro N: P 10:40» - Дудка, Сергей Владимирович (Technology audit and production reserves, 2012)
Improvement of the instrumental and technological design process of granule formation in the production of fertilizer grade «Superagro N: P 10:40» is proposed in the thesis. The results of pilot-scale tests are given